Some Evidence on Cross-Sector Effects of the Minimum Wage - Tauchen, George E. (Journal of Political Economy, 1981)
This paper tests Mincer's minimum-wage model by estimating reduced-form wage and employment equations for both the covered and uncovered sectors in nine regions of the United States. As theory predicts, in regions with comparatively small covered-sector demand elasticities, the northern and midwestern regions, the uncovered-sector wage increases after a minimum-wage hike; and in regions with comparatively large demand elasticities, the southern and western regions, the uncovered-sector wage decreases. Because of data limitations the uncovered-sector employment effect could not be estimated sharply, and so its relationship to the covered-sector demand elasticity is weak.